2020
DOI: 10.1017/s0033291720000513
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists’ attitudes to intimate and informal behaviour towards clients

Abstract: Background To avoid harming or exploiting a client, sexual and non-sexual dual relationship is generally considered as unacceptable in the psychotherapeutic relationship. However, little is known about what therapists themselves constitute as (un)acceptable intimate and informal behaviour (IIB). Methods A survey among psychotherapists in Flanders (Belgium) was conducted. Opinions about the acceptability of IIB were asked. Based on these opinions attitude groups could be determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is important to note that even when flirtation does not continue into sexual contacts, it causes serious negative mental health effects in the patient (Hook and Devereux, 2018) and damages trust in the therapist and the therapeutic relationship. It is precisely to avoid harming or exploiting a patient that more than nine out of ten therapists agree that flirting with a patient, although without further ulterior motives (we would like to add "conscious"), is an unacceptable intimate and informal behavior (Vesentini, et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that even when flirtation does not continue into sexual contacts, it causes serious negative mental health effects in the patient (Hook and Devereux, 2018) and damages trust in the therapist and the therapeutic relationship. It is precisely to avoid harming or exploiting a patient that more than nine out of ten therapists agree that flirting with a patient, although without further ulterior motives (we would like to add "conscious"), is an unacceptable intimate and informal behavior (Vesentini, et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the referral of the client to a colleague when feelings become too intense, it was observed that this referral was a suggestion from therapists to each other rather than something they actually do (7%), when comparing the survey and focus group results. Although they are not in favor of continuing therapy when in love with the client (Vesentini, Van Overmeire, et al, 2021), they seem unprepared for referring clients when encountering strong romantic or sexual feelings (Marshall & Milton, 2014). Participants in the focus groups were unclear how to exactly manage the referral of the client.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that experiencing sexual attraction (22%) and having sexual fantasies (33%) were perceived as unethical by a sizable minority of therapists (Pope et al, 1987). Another study found that the majority of therapists indicated that continuing therapy when being in love with a client (87.4%) and flirting with a client without ulterior motives (97.2%) is completely or rather unacceptable (Vesentini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%